Investigation about the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils - Mariano,Adriano Pinto (2009)
This work investigated the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils collected at three service stations. Batch biodegradation experiments were carried out in Bartha biometer flasks (250 mL) used to measure the microbial CO2 production. Biodegradation efficiency was also measured by quantifying the concentration of hydrocarbons. In addition to the biodegradation experiments, the capability of the studied cultures and the native microorganisms to biodegrade the diesel oil purchased from a local service station, was verified using a technique based on the redox indicator 2,6 -dichlorophenol indophenol (DCPIP). Results obtained with this test showed that the inocula used in the biodegradation experiments were able to degrade the diesel oil and the tests carried out with the native microorganisms indicated that these soils had a microbiota adapted to degrade the hydrocarbons. In general, no gain was obtained with the addition of microorganisms or even negative effects were observed in the biodegradation experiments.